Attenuation properties of poly methyl methacrylate reinforced with micro/nano ZrO2 as gamma-ray shields - Mahmoud T. Alabsy; Mahmoud I. Abbas; Alaa Y. El-khatib; Ahmed M. El-Khatib (Scientific Reports, 2024)
Abstract This research aimed to examine the radiation shielding properties of unique polymer composites for medical and non-medical applications. For this purpose, polymer composites, based on poly methyl methacrylate (PMMA) as a matrix, were prepared and reinforced with micro- and nanoparticles of ZrO2 fillers at a loading of 15%, 30%, and 45% by weight. Using the high purity germanium (HPGe) detector, the suggested polymer composites’ shielding characteristics were assessed for various radioactive sources. The experimental values of the mass attenuation coefficients (MAC) of the produced composites agreed closely with those obtained theoretically from the XCOM database. Different shielding parameters were estimated at a broad range of photon energies, including the linear attenuation coefficient (μ), tenth value layer (TVL), half value layer (HVL), mean free path (MFP), effective electron density (Neff), effective atomic number (Zeff), and equivalent atomic number (Zeq), as well as exposure buildup factor (EBF) and energy absorption buildup factor (EABF) to provide more shielding information about the penetration of γ-rays into the chosen composites. The results showed that increasing the content of micro and nano ZrO2 particles in the PMMA matrix increases μ values and decreases HVL, TVL, and MFP values. P-45nZ sample with 45 wt% of ZrO2 nanoparticles had the highest μ values, which varied between 2.6546 and 0.0991 cm−1 as γ-ray photon energy increased from 0.0595 to 1.408 MeV, respectively. Furthermore, the highest relative increase rate in μ values between nano and micro composites was 17.84%, achieved for the P-45nZ sample at 59.53 keV. These findings demonstrated that ZrO2 nanoparticles shield radiation more effectively than micro ZrO2 even at the same photon energy and filler wt%. Thus, the proposed nano ZrO2/PMMA composites can be used as effective shielding materials to lessen the transmitted radiation dose in radiation facilities.